Generalized Riesz Spaces Defined by Using a Sequence of Modulus Functions - Özçelik, Emine; Bektaş, Çiğdem (Seyfullah HIZARCI, 2024)
In this paper, we define a new Riesz sequence space using a sequence of modulus functions. Furthermore, we give that this space is linearly isomorphism with l(p) and determine its basis. We also give some inclusion relationships and compute ?- and ?- duals of this space.
Keywords: Numerical Analysis; Sayısal Analiz